Enhancing the Competitiveness of MSMEs Through Marketing Digitalization and QRIS Payment Implementation in Gondowangi Village, Wagir District, Malang Regency - Zaskia Nailah Atasalwa; Vahirra Annisa (International Journal of Business and Quality Research, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector in Gondowangi Village, Malang Regency, possesses resilient economic potential, yet its growth is hindered by the low digital literacy of business actors. The main constraints faced by partners include limited conventional marketing reach and inefficiencies in managing daily financial transactions. This Community Service (PkM) activity aims to accelerate the transformation and economic independence of 3 targeted MSMEs through marketing digitalization and payment system modernization. The implementation method is participatively designed through four comprehensive stages: preparation, organizing, execution, and integrated monitoring and evaluation. The results demonstrated a success rate that significantly exceeded the minimum achievement indicator of 66%. Specifically, coordinate mapping on Google Maps established an online presence that validated and increased the visibility of the partners' businesses. Furthermore, the implementation of the Quick Response Code Indonesian Standard (QRIS) payment system was fully adopted by all three MSMEs, facilitating seamless cashless transactions while encouraging the habituation of more accountable cash flow recording. In conclusion, the integration of digital mapping and cashless transaction innovations has proven effective in shifting the operational paradigm of conventional MSMEs toward an adaptive, competitive, and sustainable digital ecosystem.